Advances in Artificial Intelligence 9th Mexican International Conference on Artificial Intelligence, MICAI 2010, Pachuca, Mexico, November 8-13, 2010, Proceedings, Part I - Sidorov, Grigori.; Hernǹdez Aguirre, Arturo.; Reyes Garca̕, Carlos Alberto. (Lecture Notes in Computer Science, 2010)
This two-volume set LNAI 6437 and 6438 constitutes the refereed proceedings of the 9th Mexican International Conference on Artificial Intelligence, MICAI 2010, held in Pachuca, Mexico, in November 2010. Based on rigorous peer reviews, the program committee carefully selected 82 revised papers from 301 submissions for presentation in two volumes. The first volume includes 38 papers representing the current main topics of interest for the AI community and their applications. The papers are organized in topical sections on natural language processing; robotics, planning and scheduling; computer vision and image processing; logic and distributed systems; and AI-based medical applications.